2007
DOI: 10.1111/j.1365-3083.2007.01927.x
|View full text |Cite
|
Sign up to set email alerts
|

An Agonist Antibody Specific for CD40 Induces Dendritic Cell Maturation and Promotes Autologous Anti‐tumour T‐cell Responses in an In vitro Mixed Autologous Tumour Cell/Lymph Node Cell Model

Abstract: CD40‐mediated interactions play an important role in the response to a variety of diseases, including cancer. Engagement of CD40 on antigen‐presenting cells, namely dendritic cells (DC), by CD40L leads to maturation and up‐regulation of co‐stimulatory molecules B7.1 and B7.2 (CD80 and CD86). These molecules are requisite to subsequent antigen‐specific activation of T cells. T‐cell activation is a critical aspect of specific anti‐tumour immune responses that have become the focus of a variety of cancer immunoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Similarly, whilst profound immediate and short term effects of CP-870,893 on B cells were identified, these parameters returned to baseline by day 8 after treatment [4]. Therefore it is possible that any increase was transient and not detected by us 7 days after treatment [11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, whilst profound immediate and short term effects of CP-870,893 on B cells were identified, these parameters returned to baseline by day 8 after treatment [4]. Therefore it is possible that any increase was transient and not detected by us 7 days after treatment [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported detectable modulation of DC by CP-870,893; in particular, depletion of CD11c + CD123 dim CD14 − DC from peripheral blood, and in vitro increases in HLA-DR expression by monocyte-derived DC [10, 11]. Weekly CP-870,893 monotherapy halved circulating lymphocyte concentrations after 48 h before returning to pre-treatment levels; this depletion was not observed when dosing occurred every three weeks [4, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Although other agonistic anti-CD40 antibodies entering the clinic have been shown to activate dendritic cells with the use of model systems (19)(20)(21), we have used ex vivo assays to uniquely show biologic activity of ChiLob 7/4 on unmanipulated peripheral dendritic cells and conducted a direct comparison with a first-in-human study. Ex vivo, we have shown that ChiLob 7/4 is most potent when cross-linked and is able to activate dendritic cell to the level induced by the potent TLR ligand LPS.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that CP-870,893 activates human B cells and dendritic cells in vitro which in turn can induce T cell proliferation and cytokine production. 16-18 Here, we report that the combination of CD40 and CTLA-4 mAbs results in reinvigoration of T cells and is associated with clinical activity and acceptable toxicity in metastatic melanoma.…”
Section: Introductionmentioning
confidence: 94%